2009
DOI: 10.1002/lsm.20762
|View full text |Cite
|
Sign up to set email alerts
|

Superpulsed laser irradiation increases osteoblast activity via modulation of bone morphogenetic factors

Abstract: Background and Objective: Laser therapy is a new approach applicable in different medical fields when bone loss occurs, including orthopedics and dentistry. It has also been used to induce soft-tissue healing, for pain relief, bone, and nerve regeneration. With regard to bone synthesis, laser exposure has been shown to increase osteoblast activity and decrease osteoclast number, by inducing alkaline phosphatase (ALP), osteopontin, and bone sialoprotein expression. Studies have investigated the effects of conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 45 publications
2
40
1
4
Order By: Relevance
“…The laser irradiation used in this study was in continuous emission mode, but in an in vitro study, it was observed that superpulsed laser irradiation has osteogenic properties, inducing the expression of molecules known to be important mediators of bone formation and, as a consequence, increasing calcium deposition in human cells [23]. Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The laser irradiation used in this study was in continuous emission mode, but in an in vitro study, it was observed that superpulsed laser irradiation has osteogenic properties, inducing the expression of molecules known to be important mediators of bone formation and, as a consequence, increasing calcium deposition in human cells [23]. Fig.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that laser therapy stimulates cell proliferation and the formation of lymphatic and blood vessels [31,32], and it may improve bone mineralization [10,33,34]. The effect of laser therapy on bone regeneration has been the focus of recent researches, including in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the ability of this irradiation to stimulate both bone production and boneimplant interaction [10,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many applications of LLLT may require deep penetration of the light energy, such as: lower back, neck, and hip joint pain and inflammation. Therefore, if the power densities needs to be greater than a few mW/cm 2 and is to be delivered safely to target tissues > 5 cm below the skin surface, the effective treatment can only be achieved by using superpulsed lasers [19] . The data indicate that pulsing and particularly superpulsing is playing an important role in LLLT especially for clinical applications where deep tissue penetration is required.…”
mentioning
confidence: 99%